The Role of Translation in Developing Vocabulary Among EFL Learners Case of: Third year LMD students at Mohamed Cherif Messaadia University of Souk Ahras - Rouaida CHABBI (My University, 2026)
Abstract This study investigates the role of translation in developing vocabulary among third-year EFL students at Mohamed Cherif Messaadia University in Souk-Ahras. It aims to examine students' and teachers' attitudes toward the use of translation in vocabulary learning and teaching, to explore how translation facilitates the understanding of polysemous and figurative expressions, and to identify the difficulties students face when translating words with multiple meanings. The study hypothesizes that translation helps EFL students develop their vocabulary more effectively, that it facilitates the understanding of polysemous words in context, and that excessive reliance on translation tools may negatively affect students' ability to think directly in English. To collect data, the study employs two questionnaires administered to students and teachers, a semi-structured interview, and a vocabulary test -------------- الملخص تتناول هذه الدراسة دور الترجمة في تنمية المفردات لدى طلبة السنة الثالثة في تخصص اللغة الإنجليزية كلغة أجنبية بجامعة محمد الشريف مساعدية بسوق أهراس. وتهدف إلى دراسة مواقف الطلبة والأساتذة من استخدام الترجمة في تعلم المفردات وتعليمها، واستكشاف كيفية إسهام الترجمة في فهم التعبيرات متعددة المعاني والمجازية، وتحديد الصعوبات التي يواجهها الطلبة عند ترجمة الكلمات ذات المعاني المتعددة. وتفترض الدراسة أن الترجمة تساعد الطلبة على تطوير مفرداتهم بصورة اكثر فعاليلة ، وأنها تيسّر فهم الكلمات متعددة المعاني في سياقها، وأن الاعتماد المفرط على أدوات الترجمة قد يؤثر سلبًا على قدرتهم في التفكير مباشرةً باللغة الإنجليزية. ولجمع البيانات، اعتمدت الدراسة على استبيانين موجَّهين للطلبة والأساتذة، ومقابلة شبه موجَّهة، واختبار مفردات ----------------------------- Résumé Cette étude examine le rôle de la traduction dans le développement du vocabulaire chez les étudiants de troisième année en anglais langue étrangère à l'Université Mohamed Cherif Messaadia de Souk-Ahras. Elle vise à analyser les attitudes des étudiants et des enseignants à l'égard de l'utilisation de la traduction dans l'apprentissage et l'enseignement du vocabulaire, à explorer comment la traduction facilite la compréhension des expressions polysémiques et figuratives, et à identifier les difficultés rencontrées par les étudiants lors de la traduction de mots à significations multiples. L'étude émet l'hypothèse que la traduction aide les apprenants à développer leur vocabulaire plus efficacement, qu'elle facilite la compréhension des mots polysémiques en contexte, et qu'une dépendance excessive aux outils de traduction peut affecter négativement leur capacité à penser directement en anglais. Pour collecter les données, l'étude recourt à deux questionnaires destinés aux étudiants et aux enseignants, à un entretien semi-directif, ainsi qu'à un test de vocabulaire.
Keywords: translation; vocabulary development; EFL learners; polysemous words; vocabulary learning strategies; figurative expressions; attitudes toward translation; التر جمة، تنمية المفردات، متعلمو الإنجليزية كلغة أجنبية، الكلمات متعددة المعاني، استراتيجيات تعلم المفردات، التعبيرات المجازية، المواقف من الترجمة; traduction; développement du vocabulaire; apprenants ALE; mots polysémiques; stratégies d'apprentissage lexical; expressions figuratives; attitudes envers la traduction